Special Issue Recurrent Pregnancy Loss: Etiology, Diagnosis, and Therapy - Ole Bjarne Christiansen (MDPI AG, 2021)
The definition of recurrent pregnancy losses (RPL) varies between guidelines from different national and international scientific societies, but overall, a history of two or more (or alternatively, three or more) confirmed pregnancy losses is required for the diagnosis [...]